The association between vitamin D supplementation and the long-term prognosis of differentiated thyroid cancer patients: a retrospective observational cohort study with propensity score matching - Ahn, Jong-hyuk; Choi, Hoonsung; Kim, Su-jin; Cho, Sun Wook; Lee, Kyu Eun; Park, Do Joon; Park, Young Joo (Frontiers in Endocrinology, 2023)
Objective Benefits of vitamin D in various cancers have been reported, but its effects on differentiated thyroid cancer (DTC) have not been established. We aimed to analyze the effect of vitamin D supplementation on the prognosis of DTC. Methods A retrospective observational cohort study was conducted on 9,739 DTC patients who underwent thyroidectomy from January 1997 to December 2016. Mortality was classified as all-cause, cancer-related, or thyroid cancer-related. Patients were divided into the “VD group” (supplemented with vitamin D) and the “control group” (without vitamin D supplementation). Propensity score matching was performed in a 1:1 ratio according to age, sex, tumor size, extrathyroidal extension (ETE), and lymph node metastasis (LNM) status, and 3,238 patients were assigned to each group. Kaplan-Meier curves, log-rank test and Cox proportional hazards regression analysis were performed. Results The follow-up period was 10.7±4.2 years. Clinicopathological variables between two groups were similar except for all-cause (p<0.001) and total cancer death (p=0.001). From the Kaplan‒Meier curve and log-rank test, “VD group” had significantly favorable all-cause (p<0.001) and total cancer mortality (p=0.003), but similar thyroid cancer mortality (p=0.23). In Cox regression, vitamin D intake reduced the risk of all-cause (hazard ratio [HR], 0.617, p=0.001) and total cancer mortality (HR, 0.668, p=0.016) but had no effect on thyroid cancer mortality. Discussion/Conclusion Vitamin D supplementation was positively associated with all-cause and total cancer mortality in DTC and might be a modifiable prognostic factor for improved survival. Further research will be needed to clarify the effect of vitamin D supplementation on DTC.